Mitochondrial genome sequence of the Brazilian luminescent click beetle Pyrophorus divergens (Coleoptera: Elateridae): Mitochondrial genes utility to investigate the evolutionary history of Coleoptera and its bioluminescence - Arnoldi, F. G C [UNESP]; Ogoh, K.; Ohmiya, Y.; Viviani, V. R. [UNESP] (Elsevier, 2007)
The Coleoptera order is the richest group among Metazoa, but its phylogenetics remains incompletely understood. Among Coleoptera, bioluminescence is found within the Elateroidea, but the evolution of this character remains a mystery. Mitochondrial DNA has been used extensively to reconstruct phylogenetic relationships, however, the evolution of a single gene does not always correspond to the species evolutionary history and the molecular marker choice is a key step in this type of analysis. To create a solid basis to better understand the evolutionary history of Coleoptera and its bioluminescence, we sequenced and comparatively analyzed the mitochondrial genome of the Brazilian luminescent click beetle Pyrophorus divergens (Coleoptera: Elateridae). © 2007 Elsevier B.V. All rights reserved.
Keywords: Bioluminescence; Click beetle; Elateridae; Mitochondrial genome; Molecular phylogeny; Pyrophorus; mitochondrial DNA; beetle; bioluminescence; Coleoptera; comparative study; evolution; gene sequence; genetic analysis; genomics; mitochondrial genetics; nonhuman; nucleotide sequence; phylogeny; priority journal; Animals; Base Sequence; Beetles; Codon; DNA, Mitochondrial; Evolution, Molecular; Genome, Insect; Luminescence; Nucleic Acid Conformation; Phylogeny; RNA, Transfer; Elateroidea; Metazoa